Indian scenario and an institutional experience of fatalities in COVID-19: a narrative review - Singh, Naresh P.; Singh, Amit; Kumar, Raj; Yadav, Ramakant; Singh, Anamika; Takhelchangbam, Nilima D. (International Journal of Research in Medical Sciences, 2020)
The coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is an ongoing global pandemic that has devastated our globalized economic system. Apart from infecting 12,102,328 human beings and taking a toll of over 551,046 lives globally by the 11th of July 2020, it has fundamentally affected the way we live, work, travel, and relate to each other. Despite imposing early preventive measures, India has crossed a total caseload of 820,916 with a total death of 22,123 till-date, ranking third in the descending list of worst-affected nations. Although comparatively lower, the case fatality rate in India is 2.72% against the global fatality of 4.53%. It is an empirical fact that every process and institution must evolve to meet the needs of its time. A model for categorization of fatality among real-time reverse transcriptase-polymerase chain reaction (RT-PCR) positive COVID-19 patients has been developed at Uttar Pradesh University of Medical Sciences (UPUMS), to address the issue of patients being transferred very late in the course of the disease to level-3 facilities. The UPUMS model of categorization of fatalities of COVID-19 patients at level-3 center comprises of category-1 as ‘Institutional COVID-19 fatalities’, category-2 as ‘Imported COVID-19 fatalities’ and category-3 being ‘Imminent with Incidental COVID-19’ fatalities. This endeavor of categorizing COVID-19 fatalities is an opportunity to analyze facts and contemporary science to assess our response to this pandemic and thereby take lessons to prepare better for the future. Following proper analysis, we noted that most of these fatalities (64%) at the higher center are because of delayed referrals hence termed as imported fatalities, which need a modality of early attention and referral. However, there are fatalities which occur because of severe systemic illness like liver failure, cardiovascular accident (CVA), myocardial infarction (MI), etc. They need due treatment at a regional center. These constitute up to 18%. Authors found that actual COVID-19 deaths constitute only 18% of the total projected fatalities.